REDOX ENZYMES: From Basics to Free Radical Scavenging - Andrés, Concepción-Brindis; Mónica, Elizabeth Martínez-González (Journal of Enzymes, 2025)
Redox enzymes are a type of enzyme that catalyzes redox reactions, that is, electron transfer reactions between two chemical species. Redox enzymes are essential for many biological processes, including cellular respiration, photosynthesis, energy production, and the elimination of free radicals. They are divided into two main types: oxidoreductases and electron transferases. Oxidoreductases catalyze the direct transfer of electrons between two chemical species, while electron transferases catalyze electron transfer by cofactors. Examples of redox enzymes include cytochrome c oxidase, NADH dehydrogenase, succinate dehydrogenase, and catalase. Each of these enzymes play an important role in cellular metabolism and organism homeostasis.
Keywords: biological processes; cell respiration; free radical scavenging; oxidoreductases; transferases